Quantifying unobserved protein-coding variants in human populations provides a roadmap for large-scale sequencing projects - James Zou (Nature Portfolio, 2016)
Accurate estimations of the frequency distribution of rare variants are needed to quantify the discovery power and guide large-scale human sequencing projects. This study describes an algorithm called UnseenEst to estimate the distribution of genetic variations using tens of thousands of exomes.